Eutectic solidification in Al-Ni for L-PBF conditions: A phase-field simulation study - Apel, M.; Boussinot, G.; Döring, Markus; Schmidt, Michael (Procedia CIRP, 2020)
Two-phase solidification microstructures of regular binary eutectic alloys are composed of lamellar or rod-like pattern. The corresponding characteristic length scale λ is the spacing between lamellae or rods and results from an interplay between lateral diffusion and capillary, i.e. interfacial curvature. The basic theory had been developed by Jackson and Hunt (JH) in the 1960's and has been proven successfully for “slow” solidification. It leads to a scaling relation v.λ2=const. with v the growth velocity. In this work, we investigated eutectic solidification in Al-Ni for the faster growth rates in L-PBF processing by means of phase-field simulations. The consequences of the fast solidification on the deviation from the JH-scaling and the appearance of new features in the growth pattern are shown. Simulation results are confronted with microstructures seen in L-PBF build samples. Eventually, we discuss the opportunity to derive the local solidification speed from microstructure analysis.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Eutectic solidification; L-PBF additive process; Phase field simulations; Strongly out-of-equilibrium conditions